2009
DOI: 10.1007/s12155-009-9048-8
|View full text |Cite
|
Sign up to set email alerts
|

An Improved Tissue Culture System for Embryogenic Callus Production and Plant Regeneration in Switchgrass (Panicum virgatum L.)

Abstract: The increased emphasis on research of dedicated biomass and biofuel crops begs for biotechnology method improvements. For switchgrass (Panicum virgatum L.), one limitation is inefficient tissue culture and transformation systems. The objectives of this study were to investigate the utility of a new medium described here, LP9, for the production and maintenance of switchgrass callus and its regeneration, which also enables genetic transformation. LP9 medium is not based on Murashige and Skoog (MS) medium, the b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
113
1
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(117 citation statements)
references
References 40 publications
2
113
1
1
Order By: Relevance
“…Although both Type I and Type II embryogenic callus cultures of switchgrass have been established from various explant sources, i.e., mature caryopsis, young leaf, immature inflorescence and young seedling (Alexandrova et al 1996;Denchev and Conger 1994;Song et al 2012), reports on the longevity of embryogenic cells and the occurrence of somaclonal variations are limited. Burris et al (2009) reported that inflorescence-derived Type II callus could be maintained for more than 6 months, while the embryo viability of Type I callus was limited to less than 2 months.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Although both Type I and Type II embryogenic callus cultures of switchgrass have been established from various explant sources, i.e., mature caryopsis, young leaf, immature inflorescence and young seedling (Alexandrova et al 1996;Denchev and Conger 1994;Song et al 2012), reports on the longevity of embryogenic cells and the occurrence of somaclonal variations are limited. Burris et al (2009) reported that inflorescence-derived Type II callus could be maintained for more than 6 months, while the embryo viability of Type I callus was limited to less than 2 months.…”
mentioning
confidence: 99%
“…These effects of casamino acids and proline were similar in the ranges of 0.5-10 g l −1 and 5-100 mM, respectively (data not shown). Proline has been used at low concentrations (100-500 mg l −1 ) in combination with casein hydrolysates (Burris et al 2009;Ramamoorthy and Kumar 2012) to induce Type II calli in switchgrass. Li and Qu (2011) used proline alone at high concentration (2 g l −1 ) for friable embryogenic callus induction, and reported that all regenerated plants were albino after calli of cultivar Alamo were subcultured for 14 months.…”
mentioning
confidence: 99%
“…In this case, the pairs of tetraploid and autooctoploid lines derived from the same SE callus lines, with similar or close genetic backgrounds, could be used to identify genes that are differently regulated by chromosome doubling through expression profiling [54][55][56]. It was also recently reported that switchgrass SE callus could be generated from in vitro culture of inflorescences [57]. The inflorescence-derived SE calli should also have uniform genetic backgrounds.…”
Section: Discussionmentioning
confidence: 99%
“…Alexandrova et al (1996a) increased the efficiency of switchgrass regeneration by using immature inflorescences obtained from node cultures in aseptic conditions; one immature inflorescence can produce hundreds of spikelets of the same genotype in a single Petri dish that can be easily used as explants for callus induction. Most recently, a new medium, LP9, for the production, maintenance, and regeneration of switchgrass callus was reported (Burris et al, 2009). Callus produced on LP9 can be easily propagated, maintains its regenerability for at least six months, and is adaptable to Agrobacterium-mediated transformation (Burris et al, 2009).…”
Section: Switchgrass Regeneration Systemsmentioning
confidence: 99%